PROSPECTS FOR THE HEREDITARY FUND IN MODERN RUSSIAN LAW - Tatyana Y. Naumova; Valentina M. Bolshakova; Petr Y. Naumov (Russian Studies in Law and Politics)
The hereditary fund is a new and not fully explored form of a legal entity. Having appeared in 2018 as a bright prospect of existence in the national legal field of trusts, the inheritance fund very quickly showed all its few pluses and numerous minuses, reflecting the haste of its introduction into the Civil Code of the Russian Federation. It is worth emphasizing that the development of national inheritance law is necessary. The desire to use foreign experience in this development is reasonable and justified. However, the blind copying of trust legislation, together with the use of an inappropriate form of a Russian legal entity, namely a «fund» became a determining factor for turning a promising civil law institution into a non-working mechanism. The hereditary fund, having become the fundamental and first personal fund in the Russian Federation, after a reasonable, but not eliminating all the shortcomings of the reform in July 2021 after the entry into force of the Federal Law of July 1, 2021 № 287 «third of the Civil Code of the Russian Federation» on March 1, 2022, is now more likely a sub-institution or one of the varieties of personal funds. This article provides a detailed analysis and a scientific and legal assessment of the existence of personal and hereditary funds. The author’s position is formulated on the reasonableness of using the term «fund» when introducing trust law into the national legal field. The author defines the prospects for the existence of hereditary funds, both formal legal and practical, and also formulates proposals for improving legislation in order to increase its prestige and the interest in it of owners of large capitals in Russia.